2015
DOI: 10.1186/s12245-015-0095-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting communication in emergency departments: doctors and nurses’ perceptions of communication in a trilingual ED in Hong Kong

Abstract: BackgroundThis study investigates clinicians’ views of clinician-patient and clinician-clinician communication, including key factors that prevent clinicians from achieving successful communication in a large, high-pressured trilingual Emergency Department (ED) in Hong Kong.MethodsResearchers interviewed 28 doctors and nurses in the ED. The research employed a qualitative ethnographic approach. The interviews were audio-recorded, transcribed, translated into English and coded using the Nvivo software. The rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 21 publications
3
50
1
Order By: Relevance
“…This present study reports that both the communication competences and nursing performance of ICU staff nurses were at a fairly confident level compared with previous studies (Adams et al, ; Aslakson et al, ; Bry et al, ). Confident communication and nursing performance can be influenced by a number of factors such as cultural variables, beliefs concerning the importance of communication, and the socio‐economic background and work environment such as nurse‐to‐patient ratio, work shift, and advanced technologies and equipment in health care settings (Kounenou et al, ; Pun, Matthiessen, Murray, & Slade, ). Thus, future studies should consider multidimensional aspects and factors that influence the communication competences and clinical performance of critical care nurses.…”
Section: Discussionmentioning
confidence: 99%
“…This present study reports that both the communication competences and nursing performance of ICU staff nurses were at a fairly confident level compared with previous studies (Adams et al, ; Aslakson et al, ; Bry et al, ). Confident communication and nursing performance can be influenced by a number of factors such as cultural variables, beliefs concerning the importance of communication, and the socio‐economic background and work environment such as nurse‐to‐patient ratio, work shift, and advanced technologies and equipment in health care settings (Kounenou et al, ; Pun, Matthiessen, Murray, & Slade, ). Thus, future studies should consider multidimensional aspects and factors that influence the communication competences and clinical performance of critical care nurses.…”
Section: Discussionmentioning
confidence: 99%
“…These factors create a complicated process of multilingual communication that may be time‐intensive, difficult to document and susceptible to errors (Pun et al . ). In addition to issues associated with constant translation in a multilingual healthcare context, clinicians in Hong Kong EDs face high levels of stress due to high patient loads, limited time per patient and a lack of integration between different medical services (Tam & Lau ).…”
Section: Introductionmentioning
confidence: 97%
“…Yet the rapid pace and increasing complexity of twenty‐first century hospital care, coupled with high patient loads, make it difficult for clinicians to communicate effectively and consistently with colleagues and patients. Recent research shows that the pressure on clinicians is greater than ever (Eggins & Slade, ; Pun, Matthiessen, Slade, & Murray, ; Slade et al, ). Additional studies have shown that some doctors and nurses, particularly junior staff, are likely to remain silent in the face of perceived patient risk, even if a standardized health care communication tool is in place (Schwappach & Gehring, ).…”
Section: Introductionmentioning
confidence: 99%